2017
DOI: 10.21649/akemu.v23i1.1497
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Media Tool “Whatsapp” in Medical Education

Abstract: We are living in an era of technology where smart phones and hence social media has entered into many aspects of our life. Many professions are using social media to improve communication between colleagues. Social media tools are gaining attention in medical education as well.Objective: To explore the potential of WhatsApp as an instructional strategy for 4 th Year MBBS students in Ophthalmology. Methods:We made two groups of students on WhatsApp one for males and one for females. Topic of lecture, relevant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 3 publications
1
18
1
Order By: Relevance
“…In contrary to this the study conducted by Qudsia Anwar Dar in the department of ophthalmology shows that males students ranked it better as compared to female students. 16 But in this study, it has been observed that there is no statistically significant difference between the scores of males and females which shows that there is the equal use and preference of social media by female and male students. As the use of mobile is increasing and technology is shared by both or as it was the "study group" for understanding the subject both girls and boys might have contributed equally.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrary to this the study conducted by Qudsia Anwar Dar in the department of ophthalmology shows that males students ranked it better as compared to female students. 16 But in this study, it has been observed that there is no statistically significant difference between the scores of males and females which shows that there is the equal use and preference of social media by female and male students. As the use of mobile is increasing and technology is shared by both or as it was the "study group" for understanding the subject both girls and boys might have contributed equally.…”
Section: Discussioncontrasting
confidence: 50%
“…The exploitative supervisory relations in which established supervisors could piggyback on the efforts of emergent supervisors' publication efforts can be paralleled in mobile network providers' complaints that WhatsApp and Facebook are "freeloaders that rely on carriers' network infrastructure without spending any money to support it" (Orihuela et al, 2016). That said, contrary to the claim that students of different gender had different user preferences of WhatsApp for instruction (Dar et al, 2017), the occasional subversion of authority was a common phenomenon among both genders, irrespective of their academic level. This challenges prior research, which emphasises different foci of interactions among genders, and the re-enactment of traditional gender-related and power-related dynamics in online environments (Dixon et al, 2014;Sussman & Tyson, 2000).…”
Section: Discussionmentioning
confidence: 69%
“…Studies on the academic appropriation of WhatsApp have interrogated its use for improving learning and retaining knowledge for in‐school and out‐of‐school tasks (Ashiyan & Salehi, ), motivating and augmenting learning of medical students (Dar et al, ) and critically engaging with and questioning of information technology content (Rambe & Aaron Bere, ). While these studies employed quantitative approaches to unravel the impact of WhatsApp on student engagement, they neither foreground the significance of authentic learning contexts for engagement processes nor investigate supervision processes in these technology‐mediated environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding its teaching uses, neither the relationship between intensity of use and academic results (Rodríguez-Martínez et al, 2016;Yavuz, 2016) nor between addiction to the platform and improvement of social skills (Sánchez de Mera & Lázaro, 2017) has been shown. However, its link with motivation, planning/organization skills, improvement of the collective climate, collaboration learning, its contribution to the development of teamwork skills, and the learning of a second language have been demonstrated (Andújar-Vaca & Cruz-Martínez, 2017;Anwar Dar et al, 2017;Asterhan & Bouton, 2017;Kukulska-Hulme, 2018;Lindsay, 2016;Pérez-Jorge et al, 2018;Rosenberg & Asterhan, 2018).…”
Section: Use Of Whatsapp Messenger By Spanish Teenagersmentioning
confidence: 99%